The effect of irradiation temperature on post-irradiation strain levels in GexSi1-x/Si strained layer heterostructures - Glasko, J; Zou, J; Cockayne, D; Gerald, J; Elliman, R (1996)
Double crystal x-ray diffraction (DCXRD), transmission electron microscopy (TEM), and Rutherford backscattering spectroscopy and channelling (RBS-C) were used to study the effect of irradiation temperature and ion-energy on the perpendicular strain (epsilon perpendicular to in GexSi1-x/Si strained layer heterostructures. Room temperature irradiation was shown to increase epsilon perpendicular to. This effect was adequately modelled by assuming that irradiation caused additional strain due to excess interstitial distribution. The effects of irradiating at 253 degrees C were more complex, resulting in: a) an increase in epsilon perpendicular to when the radiation damage profile was confined to the alloy layer; or b) a decrease in epsilon perpendicular to when the damage profile extended through the alloy/substrate interface. Strain relaxation at elevated temperature is believed to be effected by loop-like defects which nucleate at or near the alloy/substrate interface during high energy irradiation.